An??lise do efeito da laserterapia de baixa intensidade na nocicep????o, express??o de mediadores inflamat??rios, neutr??filos e macr??fagos na fase aguda de artrite reumat??ide experimental em ratos - Alves, Ana Carolina Araruna (2016)
Rheumatoid Arthritis (RA) treatment in the last decades has evolved medications with cytokine inhibitors, which though they are today considered the gold standard in RA treatment, still do not guarantee complete remission from the disease or from hyperalgesia, and it is know that the Photobiostimulation (PBM) is also capable of acting on the expression of pro-inflammatory cytokines, being in this way an alternative treatment for RA. This research had as its objective the analysis and comparison of the effects of PBM in the acute phase of experimental RA in terms of nociception, of the number of inflammatory cells (neutrophils, macrophages, lymphocytes), and of the protein expression of inflammatory mediators (TNF-??, IL-6, IL-10), in the lavage and joint cartilage of rats. 49 male Wistar rats were used, with an approximate age of 90 days and a body weight varying from 250 to 300g. The animals were randomly distributed in 3 groups, with 21 animals in each experimental group (Rheumatoid arthritis group ??? RA) and the group treated with PBM (RA-LLLT), and with 7 animals in the control group. Each group was arrranged in three distinct experimental periods according to the time of euthanasia (6 hours, 24 hours, and 48 hours). For the reproduction of the lesion the animals were submitted to two inductions: the first consisted in a subcutaneous infiltration in the dorsal of each animal (in the RA and RA-LLLT groups) using 500 ??g of mBSA diluted in a solution of 100 ??L of complete Adjuvant de Freund (CFA), and 100 ??L of PBS, with this procedure being repeated weekly for 21 days. On the 28th day, an intrajoint induction was carried out with 10 ??g of mBSA diluted in 10??L of PBS, in the joint space of the right hind paw of each animal. After the joint induction, the treatment on the RA-LLLT group began, using a DMC?? brand Photon Laser III, with a wave length of ?? 808 nm, active medium of Gallium Arsenide, and Aluminium (AsGaAI), with a potency of 50 mW (potency density of 1,78 W/cm2) and area of the beam 0,028cm2. The final dose was of 2J, the density of energy of 71,2 J/cm2, and time of 40s by point. At the end of each test period (6 hours, 24 hours, and 48 hours) the animals were submitted to an evaluation of their nociception, followed by the extraction of joint lavage and joint cartilage, which were sent for analysis of the total count and differential cells, and for protein expression of the inflammatory mediators described. The results demonstrate biomodulation in the expression of neutrophils and macrophages amongst the control group and RA, as well as in the cytokines IL-6 and IL-10, contributing daily to the attenuation of hyperalgesia by the PBM.